Prenatal dietary choline supplementation modulates long-term memory development in rat offspring - Moreno, Hayarelis; de Brugada, Isabel (Nutritional neuroscience, 2021)
Background: Previous studies on preclinical models have shown that giving supplemental choline during the embryonic period improves performance on memory tasks during adulthood. However, the effects of an early intervention on the development of cognitive functions in the immature brain have not been widely studied. In addition, it has been well established that short-term memory in rats emerges at an earlier stage than long-term memory. Objective: The aim of this work was to examine the effect of prenatal dietary choline supplementation on long-term memory development in rats. Methods: In order to assess long-term memory, we used an object-recognition task, which evaluates the ability to recall a previously presented stimulus. Pregnant rats were fed with the diets AIN 76-A standard (1.1 g choline/Kg food) or supplemented (5 g choline/Kg food) between embryonic days (E) 12 and E18. On the first post-natal day (PN 0), male offspring of the rats fed with the supplemented and standard diet were cross-fostered to rat dams fed a standard diet during pregnancy and tested at the age of PN21-22 or PN29-31 applying 24-hour retention tests. Results: The supplemented animals spent less time exploring the familiar object after a 24-hour retention interval, an effect that was observed in both the group tested at PN21-22 days of age and that tested at PN29-31 days. The non-supplemented rats only showed this effect in the group tested at PN29-31 days. Conclusions: These results suggest that prenatal supplementation with choline accelerates the development of long-term memory in rats.
Keywords: development; choline; long-term memory; object recognition memory; rats; prenatal supplementation; diet; cholinergic system; WOS(2); Scopus